Pengaruh Peer Influence, Pengelolaan Pendapatan, dan Literasi Keuangan Terhadap Intensitas Bermain Judi Online di Kabupaten Ngawi - Intan Wulan Prasetiyaningsih; Novita Erliana Sari; Maretha Berlianantiya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The phenomenon of online gambling among adolescents in Ngawi Regency has shown an alarming increase. Field observations reveal that many teenagers desperately sell family assets and use their school allowance to obtain gambling deposit capital. This risky behavior is strongly driven by intense peer influence (the